A Protein Kinase C phosphorylation motif in GLUT1 affects glucose transport and is mutated in GLUT1 deficiency syndrome - Lee, Eunice E. (Mol Cell, 2015)
Protein Kinase C has been implicated in the phosphorylation of the erythrocyte/brain glucose transporter, GLUT1, without a clear understanding of the site(s) of phosphorylation and the possible effects on glucose transport. Through in-vitro kinase assays, mass spectrometry, and phosphospecific antibodies, we identify Serine 226 in GLUT1 as a PKC phosphorylation site. Phosphorylation of S226 is required for the rapid increase in glucose uptake and enhanced cell surface localization of GLUT1 induced by the phorbol ester 12-O-tetradecanoyl-phorbol-13-acetate (TPA). Endogenous GLUT1 is phosphorylated on S226 in primary endothelial cells in response to TPA or VEGF. Several naturally-occurring, pathogenic mutations that cause GLUT1 deficiency syndrome disrupt this PKC phosphomotif, impair the phosphorylation of S226 in vitro, and block TPA-mediated increases in glucose uptake. We demonstrate that the phosphorylation of GLUT1 on S226 regulates glucose transport and propose that this modification is important in the physiological regulation of glucose transport.